Product differentiation as a mediator in consumer decision-making toward lab-grown diamonds: A structural equation modeling approach - Hu, Baoquan (Edelweiss Applied Science and Technology, 2025)
As the global demand for sustainable and ethical luxury goods increases, lab-grown diamonds (LGDs) have emerged as a promising alternative to natural diamonds. This study investigates how product differentiation influences consumer decision-making regarding LGDs, with a specific focus on its mediating role between product attributes and purchase intention. Drawing on consumer behavior theory and signaling theory, a structural equation modeling (SEM) approach is employed to analyze data collected from 421 valid questionnaire responses. The results reveal that product differentiation significantly mediates the relationship between perceived value, perceived risk, and consumer trust, ultimately affecting consumers’ purchase intentions toward LGDs. Moreover, the study confirms that branding, certification, and innovation are key factors contributing to product differentiation. The findings provide theoretical insights into consumer behavior in the context of emerging sustainable products and offer practical implications for LGD companies seeking to enhance market competitiveness through strategic product positioning.